Peran Komite Sekolah dalam Meningkatkan Kualitas Sarana dan Prasarana di MTs Mambaul Ulum Musi Banyuasin - Ibrahim; Ari Muhtadin Kurniawan; Ahmad Zainuri (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2022)
This research is entitled “The Role of School Committees in Improving the Quality of Facilities and Infrastructure at MTs Mambaul Ulum Musi Banyuasin". The main objectives to be achieved through this research are: (1) to determine the role of the school committee in improving the quality of facilities and infrastructure at MTs Mambaul Ulum Musi Banyuasin, (2) to determine the factors supporting and inhibiting the role of school committees in improving the quality of facilities and infrastructure at MTs Mambaul Ulum Musi Banyuasin. In this study using a qualitative approach. In the process of collecting data, the author uses the method of interview, observation, and documentation. The results of this study indicate that: First, the role of the school committee in improving the quality of facilities and infrastructure at MTs Mambaul Ulum, includes: (1) as an advisory agency: the MTs Mambaul Ulum committee as a partner of the principal has given its considerations in every plan and programs that have been prepared by the school. (2) as a supporting agency, the role of the school committee as a supporting body for efforts to improve the quality of facilities and infrastructure at MTs Mambaul Ulum, can be in the form of financial support, energy, and mental support. For example, the committee helped build school facilities and infrastructure. (3) as the controlling agency, the school committee at MTs Mambaul Ulum controls or supervises the principal's decision-making or education planning in schools. (4) as a mediator (executive) the school committee as a liaison or mediator between the government, school parents and the community means that the aspirations of parents and the community or there is delivery of the school to the parents of students are all through the school committee. Second: The quality of facilities and infrastructure at MTs Mambaul Ulum is adequate and decent.